Battling the Buddha of love : a cultural biography of the greatest statue never built - Falcone, Jessica Marie, 1976- (Ithaca : Cornell University Press, 2018)
"This ethnography explores the controversial plans and practices of the Maitreya Project, a transnational Buddhist organization, as they worked to build the world's tallest statue as a multi-million dollar gift to India"--
Community/sangha : FPMT's transnational Buddhists -- Religious practice/dharma : global Buddhism, translation and heritage -- The statue/murti : planning a colossal Maitreya -- The relics/sarira : worship, transmission, and fundraising with the relic tour -- Aspiration/asha : hope, the future tense, and making (up) progress on the Maitreya project -- Holy place/tirtha : social life in the place of the Buddha's death -- Steadfastness/aditthana : Indian farmers resist the Buddha of love -- Loving-kindness/maitri : ethics, values and progress in the shadow of Maitreya -- Compassionate practice/karuna : advocacy anthropology and engagement -- Conclusion : faith/shraddha : guru devotion, agency and belief -- Epilogue : rebirth/samsara : the future of the Maitreya project.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: Foundation for the Preservation of the Mahayana Tradition; Foundation for the Preservation of the Mahayana Tradition; Mahayana Buddhism -- Relations; Buddhist converts; Mahayana Buddhism -- India -- Kushinagar (District); Maitreya (Buddhist deity) -- Cult -- India -- Kushinagar (District); Ethnology -- India -- Kushinagar (District); Buddhist converts; Ethnology; Interfaith relations; Mahayana Buddhism; Maitreya (Buddhist deity) -- Cult; RELIGION / Comparative Religion; HISTORY / Asia / India & South Asia; Electronic books